IMPLEMENTASI APLIKASI MOBILE UNTUK LAYANAN CATERING BERBASIS ANDROID - Alda, Muhamad; Nurhidayah, Ayyina; Nursa’adah, Nursa’adah; Zahrina, Nadhilah (Program Studi Informatika Universitas Teknologi Sumbawa, 2024)
The development of technology has advanced various aspects of life, including the culinary business. Food buying and selling applications are trending, offering convenience and efficiency in getting the desired food. This application comprises four main components, buyers, sellers, couriers, and admins. The main features include online registration, sellers uploading menus, and buyers ordering food. The culinary business continues to grow, especially fast food restaurants in urban areas, which meet the needs of a modern lifestyle. Catering is a solution for various events, offering a variety of menu choices according to client desires. The use of technology, especially Android-based applications, makes it easier to manage a culinary business, from order management to delivery coordination. The catering industry faces challenges in order management, scheduling, and inventory. However, with this application, the process becomes more efficient and effective. The food business is in great demand because of its basic human needs and high- profit potential. Catering provides food and beverage services for various purposes, meeting customer demand with menu flexibility.